2012 International Symposium on Innovations in Intelligent Systems and Applications 2012
DOI: 10.1109/inista.2012.6246946
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Marshall Stability of light asphalt concretes fabricated using expanded clay aggregate with Artificial Neural Networks

Abstract: In this study, an Artificial Neural Network (ANN) model has been developed to estimate Marshall Stability (MS) of lightweight asphalt concrete containing expanded clay. In the model, amount of bitumen (%), transition speed of ultrasound (µs), unit weight (gr/cm 3 ) were used as inputs and Marshall Stability (kg) was used as output. Developed ANN model results and the experimental results were compared and good relationship was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A broader spectrum of work was performed relating to the development of mathematical and numerical modeling [12][13][14][15][16][17]. Various research studies have used ANN to predict the results of Marshall tests for dense bituminous mixtures modified with polypropylene [8] to model the MS of asphalt concrete for changing temperatures [18]; to model stiffness modulus, MQ and MS of HMA [19]; to model MF, MS, indirect tensile strength, and stiffness of asphalt concrete with progressive conditions of temperature [20]; to determine optimum bitumen content, MS and MQ of asphalt concrete mixtures; to model fluctuation in MS with asphalt content [21]; and to model the MS of expanded clay aggregates used in light asphalt concrete [22]. Morova et al [23] used ANFIS to model MS for fiber-reinforced asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broader spectrum of work was performed relating to the development of mathematical and numerical modeling [12][13][14][15][16][17]. Various research studies have used ANN to predict the results of Marshall tests for dense bituminous mixtures modified with polypropylene [8] to model the MS of asphalt concrete for changing temperatures [18]; to model stiffness modulus, MQ and MS of HMA [19]; to model MF, MS, indirect tensile strength, and stiffness of asphalt concrete with progressive conditions of temperature [20]; to determine optimum bitumen content, MS and MQ of asphalt concrete mixtures; to model fluctuation in MS with asphalt content [21]; and to model the MS of expanded clay aggregates used in light asphalt concrete [22]. Morova et al [23] used ANFIS to model MS for fiber-reinforced asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The MS and MF of asphalt concrete have been modeled widely using the distinctive features of most common technique of AI, i.e., ANN [6,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][48][49][50][51][52][53]. These algorithms, with their abilities to recognize patterns, result in simplified engineering problems that are complex in nature [11,[54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the parameters affecting them significantly is the initial step in developing the appropriate models. After running many trials and comprehensive literature reviews [44,60,[63][64][65][66][116][117][118], MS and MF have been shown to be dependent on the following eight parameters: Both ANN and the ANFIS models were created in the MATLAB R2020b environment, utilizing the NN and FL toolbox, respectively. For the training of both models for MS and MF, 239 (70%) data points were used by a random distribution of the data, whilst the remaining 30% data points, i.e., 104, were set aside for testing and validation (15% each), in order to check the precision and generalization capability of the trained models predicting, MS and MF [119].…”
Section: Model Structure and Performancementioning
confidence: 99%
“…Furthermore, the test of MS and MF takes time, while their determination in the laboratory is also time-consuming and costly [57,58]. A number of studies have previously employed basic input parameters for the prediction of the MS and MF of asphalt pavements using ANN and ANFIS approaches [57,[59][60][61][62][63][64][65][66]. As a result, the goal of this research study is the construction of models that reliably predict the MS and MF of asphalt pavements using major input parameters that are determined simply and economically.…”
Section: Introductionmentioning
confidence: 99%